2015
DOI: 10.1039/c5an00411j
|View full text |Cite
|
Sign up to set email alerts
|

How useful is molecular modelling in combination with ion mobility mass spectrometry for ‘small molecule’ ion mobility collision cross-sections?

Abstract: Ion mobility mass spectrometry is used to measure the drift-time of an ion. The drift-time of an ion can be used to calculate the collision cross-section (CCS) in travelling wave ion mobility (e.g. Waters Synapt and Vion instruments) or directly determine the experimental CCS (e.g. Agilent 6560 instrument and many drift-tube instruments). A comparison of the experimental CCS and theoretical CCS values obtained from trajectory method He(g) parameterised MOBCAL and N2(g) parameterised MOBCAL software, for a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…7). The slope of the fit was~1.12, which is close to the reported expected slope (~1.15) obtained for molecules having a small number of rotatable bonds [24]. The average number of rotatable bonds for the entire dataset is 3.5 (median ¼ 4).…”
Section: Comparison Of the Different Models With Mobcal (N 2 )supporting
confidence: 65%
See 2 more Smart Citations
“…7). The slope of the fit was~1.12, which is close to the reported expected slope (~1.15) obtained for molecules having a small number of rotatable bonds [24]. The average number of rotatable bonds for the entire dataset is 3.5 (median ¼ 4).…”
Section: Comparison Of the Different Models With Mobcal (N 2 )supporting
confidence: 65%
“…The average number of rotatable bonds for the entire dataset is 3.5 (median ¼ 4). It has been previously hypothesized that mobcal (N 2 ) is sub-optimal and overestimates the calculated CCS for compounds with limited conformational flexibility [24], such as phenolics. To account for this bias, the predicted CCS values were corrected using the linear regression slope, referred as corrected modified mobcal (N 2 ).…”
Section: Comparison Of the Different Models With Mobcal (N 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Warnke et al 14 demonstrated that combining IM-MS and infrared multiple photon dissociation (IRMPD) spectroscopy reveals two distinct protomers of benzocaine, where depending on the protonation site (N or O), a unique N-H and O-H stretch frequencies appear. Similarly, Voronina et al 28 utilised IM-MS and cold-ion spectroscopy to study the bradykinin fragment (BK [1][2][3][4][5] 2+ ) ions elucidating cis-trans and trans-cis conformations for the more compact conformer and kinetically trapped trans-trans configuration for the larger conformer, highlighting the cis-trans isomerization of the peptide bonds during the desolvation process. In both cases, IM-MS data was supplemented with gas-phase IR experiments which in turn were supported by high-level calculations to assign potential in vacuo species.…”
Section: Mason-schamp Equation Whereas Travelling Wave Im-ms (Twims-mentioning
confidence: 99%
“…2 Both IM-MS techniques have been applied to a broad scope of species to elucidate structural information, including small drug-like molecules, 3,4 carbohydrates, 5,6 DNA and RNA, 7 proteins 8,9 and protein complexes. 9 It has also used to study protein unfolding, 8 refolding, 9,10 proton and electron transfer mechanisms 11,12 and solvent adduct effects on the protein structure.…”
Section: Mason-schamp Equation Whereas Travelling Wave Im-ms (Twims-mentioning
confidence: 99%